Network inference from glycoproteomics data reveals new reactions in the IgG glycosylation pathway - Elisa Benedetti (Nature Portfolio, 2017)
IgG glycosylation is an important factor in immune function, yet the molecular details of protein glycosylation remain poorly understood. The data-driven approach presented here uses large-scale plasma IgG mass spectrometry measurements to infer new biochemical reactions in the glycosylation pathway.